Secondary Metabolite from Endophytic Fungi Aspergillus Sp. The Leave Of Kunyit Putih (Curcuma zedoaria (Berg) Roscoe) - Muharni Muharni; Fitrya Fitrya; Widia Purwaningrum; Ahmad Yogi Nugraha (Molekul, 2016)
The compound from endophytic fungi of Aspergillus sp. from leaves of kunyit putih (Curcuma zedoaria (Berg.) Roscoe) has been isolated. Isolation begins with cultivation ofAspergillus sp. in 18 L PDB’s media (Potato Dextrose Broth) for 28 days. The liquid cultivation medium was extracted by partitioning method using ethylacetate and then evaporated. The extract was separated and purified by chromatography techniques. Elucidation stucture of the isolated compound was analysis by spectroscopic method NMR 1D and 2D. Antibacterial activity of isolated compound was tested using the disc diffusion method at concentrations 2500, 1000, 500, and 125 ppm. The isolated compounds obtained in the form of a yellow oil (24.30 mg). The 13C NMR spectrum indicated 24 signals of carbon and base on analysis spectrum DEPT 135 showed 5 signal methynes carbon, 1 signals methylene, 9 signals of methyl and 9 signals quarternary carbon. These signals from 1H and 13C-NMR suggested that this compound contained aromatic group and four carbonyl. The isolated compound show antibacterial activity at concentration 2500 ppm which inhibition zone for E. coli, S. dysenteriae, S. aureus, B. subtilis were 10.3 ; 8.3; 8.4; and 7.8 mm, respectively. Based on the analysis result of NMR 1D and 2D, the compound was methyl 6-(5'-(2"-acetoxy-2”-methylpropanoyl)-3"- methyl-2'-(3"'-methylbutanoyl)phenyl)-3-methylbutanoate and has weak antibacterial activity.